PREMENSTRUAL SYNDROME DAN PRESTASI BELAJAR MAHASISWI - Yuni Astuti Anggraini, Tyasning (Jurnal Media Ilmu Kesehatan, 2012)
The objective of research is to evaluate the effect of Premenstrual Syndrome on the Female Students? Learning Achievement in DIII Midwifery Study Program of STIKES A. Yani Yogyakarta. This study employed a qualitative method research using a case study design and is descriptivein nature. The subject of research was the female students who encounter pre menstrual syndrome. The Shortened Pre menstrual Assessment Form (SPAF) instrument was given insemester II to 212 female students, so that it can be found 11 female students encountering premenstrual syndrome. From the FGD (Focus Group Discussion) result and in-depth interview, it can be found the physical and psychological changes in the female students developing premenstrual syndrome that can affect the behavior change occurrence. The conclusion of research is that there is physical, psychological and behavior changes in the female students developing premenstrual syndrome but with their high motivation make their majority learning achievement verysatisfactory. Keywords: Premenstrual Syndrome and learning achievement.